Impact of transitioning from antibiotic use to antibiotic-free practices on broiler dead-on-arrival rates: A bayesian structural time series approach - Panneepa Sivapirunthep; Pranee Pirompud; Veerasak Punyapornwithaya; Supitchaya Srisawang; Chalita Jainonthee; Chanporn Chaosap (Poultry Science)
This study assessed the impact of transitioning from an antibiotic (AB) to an antibiotic-free (ABF) production system on dead-on-arrival (%DOA) rates during broiler transport. Data from 105,898 truckloads across 200 to 280 farms over six years were analyzed, comparing three years before (2015–2017) and after (2018–2020) the ABF transition. Decomposition analysis revealed a decline in %DOA from 2015 to 2017, followed by stability until 2019 and another decline into 2020. Seasonal fluctuations were observed, with %DOA peaking between February and April and reaching its lowest point in October. Changepoint analysis identified six significant shifts in %DOA, with the highest values occurring in 2015. Following the ABF transition, %DOA temporarily increased for about six months before stabilizing. Bayesian structural time series (BSTS) analysis showed that observed %DOA closely matched predicted values, indicating no significant effect from the ABF transition (p = 0.485; posterior probability = 51 %). These findings suggest that transport mortality can be effectively controlled without antibiotics by maintaining robust practices, such as improved sanitation, controlled rearing stocking density, optimized brooding, and enhanced pre-slaughter management.